69.8k views
4 votes
Fill in the table using this function rule. y=-3x-3 ​

Fill in the table using this function rule. y=-3x-3 ​-example-1
User Jorje
by
5.7k points

1 Answer

6 votes

Answer:

When x = -2, y = 3

When x = -1, y = 0

When x = 0, y = -3

When x = 1, y = -6

Explanation:

Given:

y = -3x - 3

Fill in the table using the following value for x

When x = -2

y = -3x - 3

y = -3(-2) - 3

y = 6 - 3

y = 3

When x = -2, y = 3

When x = -1

y = -3x - 3

y = -3(-1) - 3

y = 3 - 3

y = 0

When x = -1, y = 0

When x = 0

y = -3x - 3

y = -3(0) - 3

y = 0 - 3

y = -3

When x = 0, y = -3

When x = 1

y = -3x - 3

y = -3(1) - 3

y = -3 - 3

y = -6

When x = 1, y = -6

User Leandrojmp
by
5.5k points